You Who in Your Selves Do Comprehend All: Notes Towards a Study of Queer Union in Katherine Philips and John Milton. Issue 4 (1st October 2016) - Loscocco, Paula
ABSTRACT: This essay makes the case for a comparative analysis of the 1667 poetic volumes of Katherine Philips and John Milton. In their writings, Philips and Milton share a preoccupation with what might be called "queer union", referring less to positivist models of same-sex relations than to non-normative notions of embodied union in the various relations of homoerotic friendship, ideal marriage and erotic chastity. This essay does not undertake an analysis of Philips's and Milton's poems, except in precis form at its end. Rather, it offers critical grounds for thinking about how and why readers might embark on a comparative study of Philips and Milton as contemporaneous poets who draw on the rhetorical resources of epithalamium and elegy to assert the presence and value of queer integration amid the fragmentations of lived experience.